SYNTHESIS OF MULTICRITERIAOPTIMAL CONTROLWITH VARIABLEWEIGHTS - Lozinsky, A. O.; Demkiv, L. I. (Radio Electronics, Computer Science, Control, 2012)
In paper the dynamical systems with Takagi-Sugeno fuzzy controllerare considered. A new approach to constructing functional for multicriteria optimization is suggested, which, unlike traditional, allows the change of weight multipliers of integral quality criteria in time.